(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Nursery experiments were conducted to select the suitable biostimulants and its combination to produce quality seedlings for agroforestry and farm forestry plantation. The biostimulants such as Azospirillum, Pseudomonas and Paenibacillus were inoculated by individually and it combinations at time of seed sowing. Shoot length, root length, collar diameter, and shoot and root dry weight were recorded on 180 days after inoculations. Results showed that the total length and biomass were significantly increased in the seedlings inoculated with combined inoculation of Azospirillum, Pseudomonas and Paenibacillus when compared to control. Among the individual inoculation Azospirillum (T1) showed better response than other individual inoculation. Within double inoculations, Azospirillum +Paenibacillus (T4) was superior when compared with other double inoculations. In general, Azospirillum and its combination with other biofertilizers had more root length and biomass than other treatments.